A taxonomic review of yellow Spathoglottis (Orchidaceae) complex in Malaysia - Nordin, Farah Alia; Othman, Ahmad Sofiman; Go, Rusea; Saibeh, Kartini (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
Spathoglottis Blume is a well-known genus with a total of 44 species and widely distributed from Tropical Asia to Subtropical Asia and Pacific Islands; concentrated particularly in the Malesian region. Eight species were recorded from Malaysia and despite of a widely grown genus; Spathoglottis is a taxonomically confused genus in Orchidaceae. Confusion on several species within the Yellow Spathoglottis Complex was resolved using both morphological and molecular evidences.